2020
DOI: 10.1016/j.omtn.2019.11.038
|View full text |Cite
|
Sign up to set email alerts
|

miR-122 Exerts Inhibitory Effects on Osteoblast Proliferation/Differentiation in Osteoporosis by Activating the PCP4-Mediated JNK Pathway

Abstract: Osteoporosis is characterized by the reduction of bone mineral density and deterioration of bone quality which leads to high risk of fractures. Some microRNAs (miRNAs) have been confirmed as potential modulators of osteoblast differentiation to maintain bone mass maintenance. We aimed to clarify whether miR-122 could regulate osteoblast differentiation in ovariectomized rats with osteoporosis. miR-122 was upregulated and Purkinje cell protein 4 (PCP4) was downregulated in ovariectomized rats. PCP4 was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A number of studies have demonstrated that miRNAs exhibit roles in numerous biological processes by regulating their mRNA targets, including in cell development, tumorigenesis, cell differentiation and aging (17)(18)(19). In OS, the miRNA expression profile has been extensively studied, and a variety of miRNAs has been identified to play a role in OS, such as miR-422a, miR-145 and miR-194 (20).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that miRNAs exhibit roles in numerous biological processes by regulating their mRNA targets, including in cell development, tumorigenesis, cell differentiation and aging (17)(18)(19). In OS, the miRNA expression profile has been extensively studied, and a variety of miRNAs has been identified to play a role in OS, such as miR-422a, miR-145 and miR-194 (20).…”
Section: Introductionmentioning
confidence: 99%
“…The signi cance of c-Jun N-terminal kinase (JNK) has been validated in cell cycle regulation, apoptosis and cellular stress, and it has been also highlighted to participate in osteogenic differentiation of mesenchymal stem cells [11]. More speci cally, miR-122 elicited inhibitory effects on osteoblast proliferation through the JNK pathway [12]. The present study hypothesized that miR-497-5p may enhance the osteoblast differentiation by regulating HMGA2 and the JNK signaling pathway.…”
Section: Introductionmentioning
confidence: 81%
“…Our study also showed that miR-497-5p impaired the JNK signaling potentiation by lowering the extents of JNK phosphorylation, which was also reversed by HMGA2 upregulation. Recently, the JNK signaling pathway inhibitor was revealed to enhance the osteoblast differentiation that hampered by miR-122 mimic [12]. Pre-treatment with MAPK inhibitors reduced the protein expression of Bax promoted by IL-1α in the MC3T3-E1 cells, suggesting that the signi cance of JNK and the p38 MAPK signaling in modulating IL-1α-induced apoptosis and osteoblast differentiation of MC3T3-E1 cells [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that miR-497-5p impaired the JNK signaling potentiation by lowering the extents of JNK phosphorylation, which was also reversed by HMGA2 upregulation. Recently, the JNK signaling pathway inhibitor was revealed to enhance osteoblast differentiation [ 17 ]. Pre-treatment with MAPK inhibitors reduced the protein expression of Bax promoted by IL-1α in the MC3T3-E1 cells, suggesting the significance of JNK and the p38 MAPK signaling in modulating IL-1α-induced apoptosis and osteoblast differentiation of MC3T3-E1 cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significance of c-Jun N-terminal kinase (JNK) has been validated in cell cycle regulation, apoptosis, and cellular stress, and it has been also highlighted to participate in osteogenic differentiation of mesenchymal stem cells [ 16 ]. More specifically, miR-122 elicited inhibitory effects on osteoblast proliferation through the JNK pathway [ 17 ]. The present study hypothesized that miR-497-5p enhances the osteoblast differentiation by regulating HMGA2 and the JNK signaling pathway.…”
Section: Introductionmentioning
confidence: 99%